Ginger for nausea and vomiting in pregnancy: Randomized, double-masked, placebo-controlled trial - Vutyavanich T. (2014)
Objective: To determine the effectiveness of ginger for the treatment of nausea and vomiting of pregnancy. Methods: Women with nausea and vomiting of pregnancy, who first attended an antenatal clinic at or before 17 weeks' gestation, were invited to participate in the study. During a 5-month period, 70 eligible women gave consent and were randomized in a double-masked design to receive either oral ginger 1 g per day or an identical placebo for 4 days. Subjects graded the severity of their nausea using visual analog scales and recorded the number of vomiting episodes in the previous 24 hours before treatment, and again during 4 consecutive days while taking treatment. At a follow-up visit 7 days later, five-item Likert scales were used to assess the severity of their symptoms. Results: All participants except three in the placebo group remained in the study. The visual analog scores of post-therapy minus baseline nausea decreased significantly in the ginger group (2.1 ± 1.9) compared with the placebo group (0.9 ± 2.2, P = .014). The number of vomiting episodes also decreased significantly in the ginger group (1.4 ± 1.3) compared with the placebo group (0.3 ± 1.1, P < .001). Likert scales showed that 28 of 32 in the ginger group had improvement in nausea symptoms compared with 10 of 35 in the placebo group (P < .001). No adverse effect of ginger on pregnancy outcome was detected. Conclusion: Ginger is effective for relieving the severity of nausea and vomiting of pregnancy. © 2001 by The American College of Obstetricians and Gynecologists.